Serum IL-1β, sIL-2R, IL-6, IL-8 and TNF-α in schizophrenic patients, relation with symptomatology and responsiveness to risperidone treatment - Ayşe Binnur Erbağci; Hasan Herken; Oya Köylüoglu; Necat Yilmaz; Mehmet Tarakçioglu (Mediators of Inflammation)
Activation of the inflammatory response system and varied levels of cytokines in acute schizophrenia have been suggested by recent studies. Psychopharmacologic agents can differentially effect cytokine production, which suggests that therapeutic function of neuroleptics may involve immunomodulation.